Kompetensi Kepala Sekolah Dalam Pelayanan Administrasi Tata Usaha di MTs An-Nuur Palembang - Saputra, Ardi Tiar; Niswah, Choirun; Febriyanti, Febriyanti; Ibrahim, Ibrahim (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to analyze the competence of the school principal in administrative services at MTs An-Nuur Palembang. This research uses a descriptive method with a qualitative approach. The informants in this study consist of 8 people, including the school principal, vice principal, teaching staff, administrative staff, students, and parents. The data collection techniques used include data reduction, data presentation, data verification, and drawing conclusions. The validity of the data is ensured through triangulation, which consists of source triangulation, time triangulation, and technique triangulation. Based on the results and discussion, it is evident that the competence of the school principal in administrative services at MTs An-Nuur Palembang has been well-executed, as seen from three main aspects. The first aspect is the analysis of the improvement of administrative services, where the principal plays a key role in managing administrative services by acting as both a leader and manager who directs and organizes all administrative activities. As a manager, the principal is responsible for ensuring that all administrative processes run efficiently and effectively. The evaluation of the principal's competence shows that an effective principal must be able to provide appropriate guidance and support to all staff, including administrative staff. The impact of improved administrative services indicates that enhancing the principal's competence includes gaining a deeper understanding of school administrative processes